Resistance to amorphisation in Ca1-xLa2x/3TiO3 perovskites – a bulk ion-irradiation study. (November 2019) - Lawson, Sebastian M.; Hyatt, Neil C.; Whittle, Karl R.; Gandy, Amy S.
Abstract: The changes induced from 1 MeV Kr + and 5 MeV Au + ion irradiation at room temperature have been utilised to determine the impact of cation vacancies on the radiation damage response of bulk Ca1-x La2x/3 TiO3 perovskite structured ceramics. Perovskite systems have long been considered as candidate waste forms for the disposition of actinide wastes, and doping with multi-valent elements such as Pu may lead to cation deficiency. Based on GAXRD and TEM analysis, two regions of resistance/susceptibility to amorphisation have been confirmed with reference to CaTiO3 . Increased resistance to amorphisation has been observed for 0.1 ≤ x ≤ 0.4, with an increased susceptibility to amorphisation for x ≥ 0.5. It is proposed that these processes are induced by enhanced recovery from radiation damage for 0.1 ≤ x ≤ 0.4, and reduced tolerance for disorder/the increasingly covalent nature of the A-O bond for x ≥ 0.5. Lattice parameter analysis of the x = 0 and 0.5 samples showed a saturation in radiation damage induced volume swelling at 4.7 ± 0.1% and 1.8 ± 0.1%, respectively, while the saturation limit for the b parameter was lower than the respective a and c orthorhombic parameters. In the x = 0.2 and 0.4 samples, amorphisation was not observed, however the b parameter was found to swell to a lesser extent than the a and c parameters. Swelling was not observed for the ion irradiated x ≥ 0.6 samples. Graphical abstract: Image 1